Antarctobius bidentatus Champion 1918 ... - Posadas, Paula (Zenodo, 2008)
Antarctobius bidentatus (Champion 1918) Hypera bidentata Champion 1918: 176; Listroderes bidentatus; Kuschel 1955: 289 (Listroderes subgenus Antarctobius); Morrone 1992a: 6 (Antarctobius). ... : Published as part of Posadas, Paula, 2008, A preliminar overview of species composition and geographical distribution of Malvinian weevils (Insecta: Coleoptera: Curculionidae), pp. 1-26 in Zootaxa 1704 on page 13, DOI: 10.5281/zenodo.180856 ...